KELIMPAHAN TUMBUHAN AKUATIK DI DANAU TONDANO - J. Nebath (EKOTON, 2013)
Lake Tondano serves as a vital natural resources for North Sulawesi people, especially for those living in the Minahasa Residency and City of Manado. The Lake provides some important services namely, potable water, water irrigation, hydroelectric power, etc. It is regrettable that in the past five years, the Lake has been experiencing significant stress due to the alarmingly blooming of the aquatic vegetation in addition to sedimentation and water volume reduction problems. To address such problems, The Center of Environmental Studies Sam Ratulangi University, together with the UCE-CEPI, has been conducting an integrated research project focusing on the Tondano Watershed. This research entitled â€œ the Abundance of the Aquatik Plants in the Lake Tondanoâ€ was undertaken as a part of the joint research project above. The objective of this research was to determine and analyse the distribution and abundance of the aquatic plants in the lake Tondano. It is hoped that this research will provide some baseline information which will profoundly important to deal with eutrophication. In so doing, vegetation analysis using a systematic strip sampling was employed in this study. A further analysis was used to determine the important value, richness, diversity, and evenness indices. The findings indicated that: 1)water hychynth, Eichornia crassipes, is the most dominant aquatic plant; 2). According to the Richness Index, Tolour is the richest area among others surrounding the Lake Tondano; 3). Aquatic vegetation in Tasuka and Ranomerut areas is solely dominated by water hycynth, Eichornia crassipes.